Microscopical characters, phytochemical, and antioxidant screening of hydroalcoholic extract of Solanum xanthocarpum and Mentha arvensis - Raja, R. Ramasubramania (Journal of Medicinal Herbs and Ethnomedicine, 2015)
Mentha arvensis belonging to the family of Lamiaceae, originally the plant was imported from Japan and is therefore also known as Japanese Mint. The plant is a common garden herb and is extensively cultivated in Northern India for food seasoning as a household remedy and for its industrial used. The Solanum xanthocarpum is popularly known as Kateli, Kandakarichunda, Kandankattiri, and Indian Solanum. It has sharp and prickly branches that are densely covered with rather a minute star shaped hair. The sparsely hairy egg-shaped leaves, purple colored flowers, and round fruits. The fruit also has smooth seeds. The aim of the present study was microscopic characters of M. arvensis and S. xanthocarpum leaves, hydroalcoholic extract of the both leaves was used to qualitative screening analyses by color reaction-based identification of active constituents, to determine the total phenolic content, flavonoid content, and antioxidant potential by di-phenyl picrylhydrazyl method.